Urgency of Electronic Wallet Regulation in Indonesia - Kendry Tan; Hari Sutra Disemadi (Faculty of Law, Andalas University, 2021)
The payment system in Indonesia has undergone significant changes to date. Starting from the barter system to the existence of an electronic payment system. This change is caused by the development of technology, which has an impact on changing people's lifestyles. The payment system has been known to the public since 2014 when Bank Indonesia issued the National Non-Cash Movement (GNNT) policy. This policy aims to create a cashless society eco-system while at the same time introducing the advantages of electronic payments to the public. Electronic payments are considered safer, more efficient, and easier to track. However, electronic payments are also inseparable from their shortcomings. The electronic payment system, which is relatively new in Indonesia, will face several problems, especially with the legal system. Until now, there has been no law specifically regulating electronic payment systems, specifically E-wallet. This legal vacuum will cause problems both in terms of security and legal protection for users. This study aims to find out the problems that will arise from the E-wallet and provide solutions to the problems raised from a legal perspective. The research method used is normative juridical, using a conceptual approach and a statutory approach to review E-wallets in Indonesia. The results of this study indicate that several problems arise from electronic payments. Therefore, regulations are needed to protect user security, oversee the smooth implementation of E-wallet and maintain Indonesia's economic stability.